Data science: A Review towards the Big Data Problems. Issue 1 (June 2021) - Nasution, Mahyuddin K.M.; Sitompul, Opim Salim; Elveny, Marischa; Syah, Rahmad
Abstract: Data science is the naming of science that can change when dealing with its subject, big data, into big data science. Extraction as the main task of and based on the definition of data science requires an interpretive way of big data. This interpretation follows the characteristics of big data, namely a review of several problems that arise concerning the characters of big data is as an approach. The goal is that data and information, in information extraction or knowledge extraction from the information space, can well organize as is the case in social networks. This paper aims to provide a brief description of it.